Potential Challenges and Implications of Implementing Accrual Accounting in the Public Sector in Sri Lanka - Najimudeen, ALM (Future Science / FSH-PH Publications, 2024)
This study investigated revenue recognition, expense recording, asset presentation, and liability reporting in accrual-basis accounting in financial statements as it examined the difficulties of implementing accrual accounting in the public sector in Sri Lanka. Questionnaires were used to gather data, and ordinal regression analysis was used to examine participant replies. The findings showed a strong association between potential challenges and a number of independent variables, such as accountants' proficiency with accrual accounting, non-accountants understanding of financial statements, non-finance managers' support, regulatory and legal barriers, and the availability of qualified personnel. The results emphasized the difficulties in making the switch to accrual accounting in the public sector and offer guidance for practitioners and policymakers who want to solve these issues.